LINC00839/miR-144-3p/WTAP (WT1 Associated protein) axis is involved in regulating hepatocellular carcinoma progression - Xingqin Zhou (Taylor & Francis Group, 2021)
The present work aimed to explore LINC00839 expression level and its function in hepatocellular carcinoma (HCC), and identify the downstream molecular mechanisms. qRT-PCR (Real-Time Quantitative Reverse Transcription PCR) and western blot were employed to detect mRNA and protein levels. Functional investigations were performed by flow cytometric-based apoptosis assay, CCK8 (Cell Counting Kit-8) assay, clone formation assay, Transwell migration and invasion assay. Functional interactions between LINC00839 and miR-144-3p or miR-144-3p and WTAP were validated by dual luciferase reporter assay. siRNA (small interfering RNA) was used for LINC00839 silencing, and microRNA mimic or inhibitor were employed to modulate miR-144-3p activity. LINC00839 was upregulated in HCC cells and tissues. Silencing LINC00839 suppressed the proliferation, invasion, migration of HCC cells and induced apoptosis. Additionally, LINC00839 served as a sponge to negatively impact on miR-144-3p activity, which contributed to the high expression of WTAP (WT1 Associated Protein) and the malignant phenotype of HCC cells. Our study revealed an oncogenic role of LINC00839 in HCC, and identified miR-144-3p/WTAP axis as downstream effectors mediating the oncogenic function of LINC00839. LINC00839 might serve as a potential therapeutic target and prognostic marker for HCC.